Pengembangan Model Permainan Berbasis Outbound dalam Menanamkan Karakter Disiplin Kelas IV SDN Bugangan 01 - Denia Dwi Oktavian; Asep Ardiyanto; Ferina Agustini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The background of this research is that there are still violations by students against the rules and habits that exist in schools. The formulation of the research problem is how is the game model and the feasibility of the outbound-based game model in instilling the disciplinary character of SD N BUGANGAN 01? This study aims to determine the development of game models and the feasibility of outbound-based game models in instilling discipline character. The research method used in this research is research and development proposed by Sugiyono. Quantitative descriptive data analysis techniques are used to analyze data in the form of numbers derived from validation by material experts, models, teachers, students and observation sheets. The feasibility of the model is obtained through model validation, materials, teachers, students and observation sheets. The validation results obtained were 90% and 88% of the model expert validators in the "very feasible" category. Obtained 84% in the "very feasible" category and 80% in the "proper" category from the material expert validator. The teacher's response questionnaire obtained 94% in the "very feasible" category. The student response questionnaire obtained 93% in the "very feasible" category and 89% from the observation sheet in the "very feasible" category.Â